Effect of varying levels of fibre and starch in calf starters containing finely ground maize grain on performance of pre-ruminant calves: Varying kevels of fibre and starch in calf starters on performance of pre-ruminant calves - Govindaraj, Alexander; Mekala, Tirupathi; D, Nagalakshmi; Rathod, Suresh (Indian Journal of Dairy Science, 2023)
The nutrient composition and particle size of calf starter play a major role in shaping appropriate rumen development and starter intake and average daily gain in pre-ruminant dairy calves. Hence, a feeding trial was conducted to assess the effect of feeding calf starters containing finely ground maize grain with varying levels of fibre and starch on performance of pre-ruminant dairy calves fed no roughage. Three iso-nitrogenous calf starters containing different levels of finely ground maize grain and soyabean hulls (maize:soyabean hulls 40:10; 30:20; 20:30) were evaluated through a feeding trial using 18 Holstein Friesian crossbred female calves (average body weight 34.19 ± 0.94 kg). The calves were divided into three groups of 6 calves each in a completely randomized design. Milk was offered to calves twice daily from fourth day of age upto 63 day of age as per the step up/step down milk feeding schedule. In addition, calves in each group were offered respective calf starters individually ad libitum from 3 to 63 day of age. Daily starter intake and fortnightly body weight of calves were recorded during the trial. The calves were monitored for rumination from third day of age until rumination was noticed. Blood samples were collected from calves on 63 day of age for estimation of various biochemical constituents. The level of starch and fibre in calf starters containing finely ground maize grain (57.72% of particles with the size of 1.18 mm above) had no influence on overall calf starter dry matter intake (401.89 to 424.68 g/d), average daily gain (0.660 to 0.700 kg/d), feed conversion efficiency, feed cost/kg gain, initiation of rumination and blood biochemical constituents in pre-ruminant dairy calves. Maximum pre-weaning average daily gain (700 g/d) can be achieved in Holstein Friesian crossbred female calves through feeding milk by step up/step down method and calf starter containing finely ground maize grain and soyabean hulls in the ratio of 20:30 without offering any roughage.